Prediction of Impact Response for Reinforced Concrete Beams by Numerical Simulation Method - Ahmad Rahmati Alaei; Seyed Mohammad Hossein Khatami (Journal of Rehabilitation in Civil Engineering)
Brittle characteristics, low tensile strength, and rapid crack propagation upon exposure to impact loads are some of the issues associated with concrete. This study predicts reinforced concrete (RC) beam failure modes under impact loads using experimental tests and numerical simulations. This paper simulates the drop test of a hammer using the nonlinear finite element method (FEM) and the powerful FE analysis software LS-DYNA. The developed model, unlike other numerical research, boasts a high computational speed and can effectively simulate real impact test conditions, like a vehiclecollosion with a bridge barrier. Also, the material models introduced for concrete and steel can be used in low to high strain rates for impact with different loading rates (LR).The components of the model include concrete, rebar, stirrup, and hammer. The reinforcement is modeled by beam elements, while the other parts consist of solid elements with an average size of 10mm. CONCRETE DAMAGE and PEICEWISE LINEAR PLASTICITY are used for describing the material behavior of concrete and rebar-stirrup, respectively. The interaction between parts, due to the different behavior of their materials, is carefully considered in the analysis. The difference in maximum displacement at beam midpoint between the impact test and the numerical simulation is less than 8%, highlighting an acceptable agreement between the results. The plastic strain contour for the RC sample test S1616 shows flexural failure modes at a drop height of 0.15 meters. The effects of the loading rate (LR) and concrete compressive strength are discussed. For every 10 MPa improvement in concrete compressive strength, mid span displacement decreased by about 10%. Impact force increases by roughly 31% at high loading rates (LR = 10 m/s), and compressive strength ranges from 32 MPa to 52 MPa.